A disciplina História da Matemática: Um estudo sobre as concepções do professor do Ensino Superior - Ferreira, Terezinha Francelino (2005)
This study had how objective investigate the conceptions of the professors with relation to disciplines History of the Mathematics in superior education, in order to answer some questions of research: Why they consider disciplines it of important History of the Mathematics in the course ? How do they developed theirs classes ? As pupils evaluate? For this, a quality research of character was developed, with a group of professors who give lessons of History of the Mathematics in institutions of Superior Education. When analyzing the speeches of these professors, was searched understand its pratical conceptions and when treating History of the Mathematics. The study of the conceptions of the searched professors it made possible to detach the paper of History of the Mathematics in the formation of the professors, as also reflections on the development of the Mathematics by the inhrent difficulties of the society and the contribuition of History in the development of the maturity and criticism of the pupil.